EFFECTS OF USING PROPOLIS IN PREVENTING RELAPSE IN ORTHODONTIC TREATMENT - Rajagukguk, Kezia Revi; Sagita, Kintan Ratu; Hermawan, Laras Meisitha; Pakpahan, Evie Lamtiur (Moestopo International Review on Social, Humanities, and Sciences, 2023)
Background: Relapse during orthodontic treatment often occurs. Herbal ingredients have many benefits, one of which is propolis extract which contains flavonoids, saponins and CAPE, which can increase the number of fibroblasts and osteoblasts in the traction area which play a role in bone remodeling, thereby preventing relapse during orthodontic treatment.Purpose: to find out more about herbal ingredients that can prevent relapse during orthodontic treatment.Methode: analyzing research journals from the Google Scholar and Research Gate databases. The research analyzed was the effect of using the herbal ingredient propolis on tooth movement in preventing relapse in orthodontic treatment carried out on animals.Conclusions: This report reveals that the use of propolis at a certain concentration and in combination with HBOT can prevent relapse in orthodontic treatment by accelerating the formation of osteoblasts and fibroblasts.